Effect of pasteurisation on the concentrations of vitamin D compounds in donor breastmilk. (2nd January 2016) - Gomes, Fabio P.; Shaw, P. Nicholas; Whitfield, Karen; Koorts, Pieter; McConachy, Helen; Hewavitharana, Amitha K.
Abstract: Premature infants are the main recipients of pasteurised donor human milk (PDHM), when their mothers are unable to provide their own. In this study, we evaluated the effect of pasteurisation on the concentrations of vitamin D compounds in donor breastmilk. Milk samples were obtained pre- and post-Holder pasteurisation. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to analyse the samples for vitamins D2 and D3 (D2 and D3 ) and 25-hydroxyvitamins D2 and D3 (25(OH)D2 and 25(OH)D3 ). The significance of differences in vitamin D concentrations between the two groups of milk samples was assessed using the Wilcoxon matched-pairs signed rank test, in which p < 0.05 was considered significant. Pasteurisation resulted in a significant reduction ( p < 0.05) in the content of D2, D3, 25(OH)D2 and 25(OH)D3 . The losses ranged from 10% to 20% following pasteurisation.